2019
DOI: 10.1108/cdi-01-2019-0023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of family encouragement on migrant workers’ return-to-hometown intention and turnover

Abstract: Purpose Given migrant workers’ critical role in the Chinese economy, the increasing number of migrant workers who leave their organizations and return to their hometown has caused severe socioeconomic issues in China. The purpose of this paper is to contribute to migrant worker literature by revealing the micro-mechanism underlying migrant workers’ return-to-hometown intention and turnover. Design/methodology/approach Data were collected from a convenience sample from seven Chinese companies that employed mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…When employees receive support from their superiors, they will have more resources to deal with the problems of work-family conflict, maintain their job and life satisfaction, and retain their current jobs (Zhang, Rasheed, & Luqman, 2020). Li et al (2020) claim that it is important for organizations to take care of migrant workers' families, their needs, and career-related concerns. Such a relationship would positively affect employees' emotions and their perception of the organization.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…When employees receive support from their superiors, they will have more resources to deal with the problems of work-family conflict, maintain their job and life satisfaction, and retain their current jobs (Zhang, Rasheed, & Luqman, 2020). Li et al (2020) claim that it is important for organizations to take care of migrant workers' families, their needs, and career-related concerns. Such a relationship would positively affect employees' emotions and their perception of the organization.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%
“…Saefullah describes the types of modern jobs in the city that attract migrant workers as professionals to work in the formal sector and settle in the city [24]. Types of jobs in the city require professional workers who have certain skills and expertise with a high level of education for professionals who have specific expertise (specialization) who work in formal employment.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…While on the other hand, the pattern of household, food, and non-food consumption expenditure in Mamuju Regency, respectively between 52.76 percent and 47. 24 percent, shows that the standard of living of the people in Mamuju Regency is still relatively low [5]. Pay attention the above; there appears that a contradiction between the pattern of household consumption expenditure and the high average household expenditure in urban areas, so there is an issue that lodging costs in Mamuju Regency, especially in Mamuju District, are relatively higher compared to lodging costs in the City Makassar or other districts in South Sulawesi.…”
mentioning
confidence: 98%
“…Haug ( 17 ) examined the effect of social capital in the inflow region on international immigrants' return intentions. Li et al ( 18 ) explored the relationship between familial factors and the return intentions of migrant workers. Studies by Gu et al ( 19 ) found that factors influencing the return intentions of migrant workers in China to return home, including familial relationships, housing, society and space.…”
Section: Introductionmentioning
confidence: 99%